Refusing the Favor : the Spanish-Mexican Women of Santa Fe, 1820-1880. - Gonzalez, Deena J. (Oxford University Press, 2001)
Refusing the Favor tells the little-known story of the Spanish-Mexican women who saw their homeland become part of New Mexico. A corrective to traditional narratives of the period, it carefully and lucidly documents the effects of colonization, looking closely at how the women lived both before and after the United States took control of the region. Focusing on Santa Fe, which was long one of the largest cities west of the Mississippi, Deena Gonzalez demonstrates that women's responses to the conquest were remarkably diverse and that their efforts to preserve their culture were complex and lon.